Produktivitas kalkun (Meleagris gallopavo) yang diberi pakan tambahan daun singkong dan ampas tahu dalam ransum - Muhammad Adil Fasha; Sari Suryanah; Elly Amalia; Syifa Nurjannah; Nilawati Widjaja; Hilman Permana (University of Insan Cendekia Mandiri, 2024)
Turkey is one of the poultry commodities with the potential to be a source of animal protein for the community. Optimal turkey productivity must be supported by the provision of rations that in quality and quantity can meet the needs of the livestock, including by providing additional feed that is relatively cheap but has high nutritional value. This research aimed to determine the effect of providing additional feed with cassava leaves and tofu dregs in the ration on turkey productivity and to obtain the percentage of additional feeding with cassava leaves and tofu dregs in the ration that produces the best productivity. The method used experimental and Completely Randomized Design, 3 treatments, namely P1: giving 90% basal ration + 5% cassava leaves + 5% tofu dregs, P2: giving 80% basal ration + 10% cassava leaves + 10% tofu dregs, and P3: giving 70% basal ration + 15% cassava leaves + 15% tofu dregs, replicated 8 times, each replication consisting of 4 turkeys. The variables observed were ration consumption, body weight gain, and ration conversion. Data were analysed using ANOVA (0,05) and Duncan's Multiple Range Test. Based on the research results, providing cassava leaves and tofu dregs in the ration had a significant effect on turkey productivity. Providing additional feed with cassava leaves and tofu dregs as much as 5% in the ration produces the best ration consumption, body weight gain, and ration conversion, approximately 5,087.06 g/birds, 2,883.59 g/birds, and 1.80.